"DITARIK " Pelatihan Penyusunan Laporan Keuangan Digital Menggunakan Aplikasi MONEY LOVER Pada Usaha UMKM ES Jagung Next Level - Surahman Julizar Saputra; M. Rahman Febiliansa; Yun Fitriano; Lidya Gustina Putri (Jurnal Dehasen Mengabdi, 2025)
The development of technology is very influential on the development of technology today, especially in today's digital era. Technology has had a significant impact on human life in the social, economic and cultural fields. Technology has changed business processes to be more efficient and effective so as to increase productivity and business growth. One of them is the development of micro, small. And medium (UMKM) which are already many in Indonesia, the background of the formation of UMKM in Indonesia is the rapid development of technology. One of the reasons we took the title “Digital financial preparation training using the money lover application at the next level corn ice UMKM business” is because the ice UMKM business has not used financial reporting records using digital applications. This implementation is carried out by means of socialization using the money lover application in the MSME Ice business.